Analisa Manajemen Waktu Pada Pengelolaan Administrasi Di Dinas Perhubungan Provinsi Sumatera Utara Dengan Critical Path Method (CPM) - Lingga, Eva Ridya Wanti; Atika Nadila; Mingka, Muhammad Farhan; Riezky Meiliza; Ismail Husein (Jurnal Pengabdian Masyarakat, 2022)
Practical work (KP) is an academic activity that aims to shape student learning and develop and improve a qualified workforce. By participating in practical work (KP) it is hoped that istudents will be able to add knowledge, skills and experience in preparing themselves to enter the real world of work. The problems that occur in the administration section are delays in the administrative process. Therefore, practitioners try to use the Critical Path Method to complete administrative processes to make them more efficient by determining the critical path to inefficient work processes. the critical path can be found by looking at the total float resulting in a sum equal to 0 which is a critical activity and the critical path is found as follows: "1-3-4".